Non-lethal detection of mtDNA from the monogenean Gyrodactylus mutabilitas which recorded for the first time from the gill mucus of Cyprinus carpio, Iraq (Revista de Ciências Agroveterinárias, 2024)
The monogenean species of the genus Gyrodactylus are harmful to the common carp Cyprinus carpio. In this study fish sampling were collected from al-Tarmiyahm fish farm, Baghdad Iraq. The presence of the monogenean Gyrodactylus mutabilitas is reported in the present study for the first time on the gills of the common carp. Morphological characterization and measurements of this parasite are provided. The distribution of this monogenean on the gill arches of the hosts revealed a specific right-side preference, with a notable affinity for the second gill arches. Typically, accurate diagnosis of the monogenean relies on traditional methods by their morphology and it can only be achieved by fish post-mortem dissection. To support common carp conservation and management in the fish farm, a non-lethal method for pathogen detection is urgently needed. In this study, gill swabbing  proved to be a promising technique for obtaining Gyrodactylus mutabilitas DNA samples.Fisheries managers may find this method be a useful tool to assess infection status which may prevent the spreading of any possible infection.
Keywords: Gyrodactylus mutabilitas; common carp; non-lethal sampling; site preference; Iraq